2020
DOI: 10.1038/s41598-020-72770-5
|View full text |Cite|
|
Sign up to set email alerts
|

A link between appendectomy and gastrointestinal cancers: a large-scale population-based cohort study in Korea

Abstract: An association between appendectomy and subsequent gastrointestinal (GI) cancer development has been postulated, although the evidence is limited and inconsistent. To provide clarification, we investigated the link between appendectomy and GI cancers in a large nationwide appendectomy cohort. This cohort was derived from the claims database of the National Health Insurance Service in South Korea and comprised 158,101 patients who had undergone appendectomy between 2007 and 2014. A comparison cohort of 474,303 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The cohort with appendicitis was shifted to younger ages, producing an expected count of 3.35 cases and a standardized incidence ratio (SIR) of 3.28 with a 95% CI of 1.82-5.92. This is generally consistent with the majority of the existing literature (summarized in Table S3), which suggests that older patients presenting with appendicitis have an increased risk of bowel cancer in the first few years after appendicectomy [9,10,12,15,16]. Two large population-based studies suggest the risk is around double that of the age-standardized background population [9,12].…”
Section: Incidencesupporting
confidence: 88%
See 1 more Smart Citation
“…The cohort with appendicitis was shifted to younger ages, producing an expected count of 3.35 cases and a standardized incidence ratio (SIR) of 3.28 with a 95% CI of 1.82-5.92. This is generally consistent with the majority of the existing literature (summarized in Table S3), which suggests that older patients presenting with appendicitis have an increased risk of bowel cancer in the first few years after appendicectomy [9,10,12,15,16]. Two large population-based studies suggest the risk is around double that of the age-standardized background population [9,12].…”
Section: Incidencesupporting
confidence: 88%
“…There has also been discordance in the literature regarding the actual risk of CRC after appendicitis. A number of retrospective series have suggested an increased risk of CRC in older patients with appendicitis [6][7][8][9][10]; however, other studies have shown no difference [11] or implied that any difference may be artefactual [12].…”
Section: Introductionmentioning
confidence: 99%
“…Seven of them noticed a significantly higher CRC risk in the appendectomy group 18,21,23,24,28,32,33 while seven established no difference between the risk of CRC in patients with or without appendectomy. 13,16,19,22,31,34,35 One of them even observed that appendectomy might be a protective factor for CRC. 30 Detailed results are available in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, inflammatory responses are not only of interest during appendicitis. The appendix has been associated with multiple diseases, including colorectal cancer, ulcerative colitis, and Parkinson's disease, although via mechanisms unknown [44][45][46][47][48] . Additional research regarding the environment of the human appendix may reveal new insights into both the function of this organ as well as insights into the pathophysiology of multiple human diseases.…”
Section: Discussionmentioning
confidence: 99%